The art of computer programming, volume 4, fascicle 5 : mathematical preliminaries redux; introduction to backtracking; dancing links - Knuth, Donald E. (Boston : Addison-Wesley, 2020)
"This fascicle covers three separate topics: 1. Mathematical Preliminaries. Knuth writes that this portion of fascicle 5 "extends the 'Mathematical Preliminaries' of Section 1.2 in Volume 1 to things that I didn't know about in the 1960s. Most of this new material deals with probabilities and expectations of random events; there's also an introduction to the theory of martingales." 2. Backtracking: this section is the counterpart to section 7.2.1 which covered the generation of basic combinatorial patterns. This section covers non-basic patterns, ones where the developer needs to make tentative choices and then may need to backtrack when those choices need revision. 3. Dancing Links: this section is related to 2 above. It develops an important data structure technique that is suitable for backtrack programming described above"--
Includes index.
CSE
Keywords: Computer programming; Computer algorithms; Computer science